2018
DOI: 10.3390/e20060449
|View full text |Cite
|
Sign up to set email alerts
|

Sample Entropy of the Heart Rate Reflects Properties of the System Organization of Behaviour

Abstract: Cardiac activity is involved in the processes of organization of goal-directed behaviour. Each behavioural act is aimed at achieving an adaptive outcome and it is subserved by the actualization of functional systems consisting of elements distributed across the brain and the rest of the body. This paper proposes a system-evolutionary view on the activity of the heart and its variability. We have compared the irregularity of the heart rate, as measured by sample entropy (SampEn), in behaviours that are subserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…Any behaviour can be described as a dynamic process of actualization of functional systems and formation of new functional systems (learning) within the organism-environment interactions. In this view, HRV originates in co-operation of cardiovascular and other components of actualized functional systems, including neuronal groups, and reflects complexity of the dynamics of current organism-environment interactions ( Bakhchina et al., 2018 ). Overall, complex interactions with the environment, including those in social contexts, require a complex dynamics of psychophysiological processes supporting this particular behaviour, which is reflected in higher complexity of HRV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Any behaviour can be described as a dynamic process of actualization of functional systems and formation of new functional systems (learning) within the organism-environment interactions. In this view, HRV originates in co-operation of cardiovascular and other components of actualized functional systems, including neuronal groups, and reflects complexity of the dynamics of current organism-environment interactions ( Bakhchina et al., 2018 ). Overall, complex interactions with the environment, including those in social contexts, require a complex dynamics of psychophysiological processes supporting this particular behaviour, which is reflected in higher complexity of HRV.…”
Section: Discussionmentioning
confidence: 99%
“…Complex interactions with the environment require a complex dynamics of psychophysiological processes, which can be described using non-linear measures, such as PE and other entropy measures. For example, in our previous work we demonstrated that complexity of HRV was higher when individuals were solving more difficult tasks, such as using foreign language as opposed to using native language and completing sentences about complex mathematical concepts as opposed to sentences about simple everyday concepts (see Bakhchina et al., 2018 ). Thus, our theoretical approach and experimental results suggest that higher complexity of HRV corresponds to more complex physiological processes supporting individual behaviour in the environment.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…SampEn is a time series complexity measure method, which has the advantages of simple calculation and fast speed [ 38 , 39 , 40 , 41 ]. The larger the sample entropy, the more random or irregular the sequence and the lower the self-similarity.…”
Section: Methodsmentioning
confidence: 99%
“…Bakhchina et al were interested in the “mind–body” relationship and explored how the system organization of behavior could be reflected in the irregularity of the heart rate, as measured by sample entropy [ 8 ]. Thus, they proposed a model explaining HRV in relation to neuronal processes in the brain.…”
Section: Applications Of Sample Entropy or Its Derivativementioning
confidence: 99%